The Controversial Application of Competences in Teacher Training at University - Rosario Mérida Serrano (Universitat Politècnica de València, 2013)
This paper presents a conceptual clarification of the term 'competences', outlining the authors' personal stance and examining different theoretical currents which offer differing views of this construct. Its polysemy and ambiguity generate different conceptions and, consequently, encompass different educational practices within university education. An exhaustive characterisation of this concept helps to identify its significant features: its holistic, comprehensive, contextual, axiological, transferable and evolutionary nature. This paper shows the potential of competences to offer frameworks of reference for the new model of university teaching proposed in the European Higher Education Area. Hence, competences appear as broad ends in themselves which frame the purposes and formative and professional profile of university course programmes, whilst at the same time facilitating the selection of contents, understood as cultural media, which in turn facilitate the acquisition of relevant, in-depth, interdisciplinary, flexible and creative knowledge. Competences allow us to design learning situations and to choose methodological principles which emerge from involving students in research processes in order to acquire new knowledge. Similarly, evaluation is affected by the inclusion of competences in the curriculum, requiring the application of an approach to training which is materialised through the use of different instruments to evaluate the processes and not just academic results. Finally, the paper analyses certain circumstances which have hindered the real application of competences in scenarios of higher education, proposing the RIECU network as an example of good practices for the development of professional competences in prospective Pre-Primary school teachers.